Peningkatan Promosi Digital Desa Melalui Keterlibatan Pemuda Desa - Seli Septiana Pratiwi; Desy Santi Rozakiyah; Nanda Harda Pratama Meiji; Deny Wahyu Apriadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Local and foreign tourists can be persuaded to visit attractions offered through social media. Wonokitri Village, one of the gateways to Bromo Tengger Semeru National Park (TNBTS), has resumed tourism promotion through social media. There are barriers to managing social media, including owning and managing social media. The charity will be implemented through outreach and direct support to village youth by involving Pokdarwis Wonokitri Village as a participant. The goal is to make village promotions more inclusive and allow local communities to manage social media to attract tourists. Philanthropic activities include direct participatory efforts. The first step in maximizing our work was to work with POKDARWIS members to identify the key constraints and needs of the local community. Next, a discussion was held on the content that characterizes the village's potential. In addition, local village youth are supported to create engaging social media content for tourists, especially in the form of photographs. The implementation team also gained an understanding of the different functions of social media used and how to best utilize them to promote digital village tourism.